Hunger and malnutrition in a COVID-19 environment: What are the effects amidst rising food prices in sub-Saharan Africa? - Bernadette Dia Kamgnia; Kan David N'Dri (Economies, 2025)
The COVID-19 pandemic intensified existing structural challenges in Africa, including poverty, weak healthcare systems, and fragile agricultural supply chains. Consequently, examining its effects remains a critical area of study. This research investigates the effect of food prices on the prevalence of malnutrition in the context of the COVID-19 pandemic in sub-Saharan Africa. The findings indicate a significant long-term relationship between the number of COVID-19 cases, food prices, and the prevalence of undernourishment. Specifically, increases in food prices are associated with a rise in undernourishment rates over the long term. These results are corroborated by estimations using Fully Modified Ordinary Least Squares (FMOLS). To mitigate malnutrition in the face of potential future health shocks, governments could create and operationalize food price stabilization funds to cushion against sharp increases in food prices. These funds can be used to subsidize key staples during periods of price volatility, ensuring affordability for vulnerable populations.
Keywords: C32; C54; I15; 330; health crises; malnutrition; food prices; panel ARDL